Nature of man in the problem field of biocultural anthropology - Salata, H. V. (History of science and technology, 2014)
This article attempts to analyze biocultural principle in human nature in the context of biocultural anthropology. Biocultural anthropology overcomes the one-sidedness of biological and sociological conceptions of human nature, which was caused by inconsistencies in the nature of human as biological and social/cultural being. Within this paradigm, person acts as a connecting link between the natural world and the world of culture. His humanness is defined simultaneously by two components - biological and cultural, and none of them prevails.